Tlingit woman at loom making Chilkat blanket, as man holds pattern board, Klukwan, Alaska, ca. 1909 - University of Washington Libraries
Woman in skirt & blouse kneels at loom outdoors, starting a Chilkat blanket. Standing at right is a man displaying the wooden pattern board. In background is a small wooden building. Photographer possibly Harland Smith. Note from American Museum Journal, v.10, p.31-48, Feb 1910: Chilkat blanket (unfinished) and pattern board, Kluckwan, Alaska. Northwest Miscellany, v.1, item 33